PENINGKATAN KEMAMPUAN NUMERASI SISWA KELAS 2B SDN SUKUN 3 MALANG MELALUI MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA DOMINO - Tiara Putri Maulidya, Adilla; Nur Kumala, Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low numeracy skills among students remain one of the major challenges in mathematics learning, particularly in Grade 2B of SDN Sukun 3 Malang. Many students experience difficulties in understanding number concepts, performing basic arithmetic operations, and solving numeracy problems related to daily life. This study aimed to improve students' numeracy skills through the implementation of the Problem-Based Learning (PBL) model assisted by Number Domino Media. The study employed Classroom Action Research (CAR) consisting of two cycles, with each cycle including the stages of planning, action, observation, and reflection. The participants were Grade 2B students of SDN Sukun 3 Malang in the 2025/2026 academic year. The findings revealed a gradual improvement in students' numeracy skills throughout the implementation of the learning cycles. The application of the PBL model combined with Number Domino Media enhanced students' participation, collaboration, and understanding of numeracy concepts through meaningful and engaging problem-solving activities. Therefore, the Problem-Based Learning (PBL) model assisted by Number Domino Media was found to be effective in improving the numeracy skills of Grade 2B students at SDN Sukun 3 Malang.